A self-cleaning superhydrophobic coating for N-TiO2 photocatalytic surface and its fluorine-free preparation method
Patent Information
- Application Number
- CN202411000297.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-24
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-07-24
AI Technical Summary
在长时间的户外使用中,随着户外使用时间的延长,许多超疏水表面与水的接触角减小,导致疏水性大大降低
[0037](1)本发明提供的制备方法简单、易控,制备的PDMS/STA/N-TiO2涂层超疏水表面与水的接触角大、超疏水性强、稳定性好,具有自清洁能力,能够在可见光下实现对亚甲基蓝染料等有机污染物的有效降解。
Smart Images

Figure CN118931377B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanomaterials and superhydrophobic materials technology, and specifically relates to an N-doped TiO2 photocatalytic surface self-cleaning superhydrophobic coating and its fluorine-free preparation method. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] Due to industrialization, atmospheric turbidity has increased. Outdoor walls and glass, exposed to wind and rain, easily accumulate pollutants, forming grime and reducing aesthetics and light transmittance. Therefore, the development of self-cleaning surface materials with superhydrophobic properties has become a widely discussed and important issue.
[0004] Photocatalytic oxidation technology, due to its advantages of high efficiency, low cost, and environmental friendliness, has become a widely researched process for pollution control. On traditional hydrophobic coatings, some pollutants inevitably remain. Adding photocatalytic materials to the coating material is an effective way to degrade these residual pollutants. For example, G. Yamauchi discovered that adding a small amount of TiO2 powder to a superhydrophobic transparent coating to improve the durability of the superhydrophobic surface can give the coating excellent self-cleaning properties and allow it to function for a long time, maintaining its superhydrophobicity for extended outdoor use.
[0005] However, traditional hydrophobic modification processes often use fluorine-containing substances, which have a significant impact on the environment and human health. Currently, some researchers are dedicated to the development of fluorine-free superhydrophobic coatings to enable their green production and application. However, fluorine-free superhydrophobic coatings prepared using existing technologies often lag significantly behind fluorine-containing superhydrophobic coatings in terms of superhydrophobic performance. Therefore, preparing fluorine-free superhydrophobic coatings that meet current green and environmentally friendly requirements is a critical issue that urgently needs to be addressed.
[0006] Meanwhile, the properties of superhydrophobic surfaces are primarily determined by their surface microstructure. During prolonged outdoor use, the contact angle between many superhydrophobic surfaces and water decreases with the extension of outdoor time, leading to a significant reduction in hydrophobicity. Therefore, developing a novel fluorine-free superhydrophobic material that increases the contact angle between the superhydrophobic surface and water, thereby enabling the material to simultaneously possess superhydrophobicity and excellent photocatalytic properties, and to autonomously degrade and remove pollutants, is a technical problem urgently needing to be solved by those skilled in the art. Summary of the Invention
[0007] To address the aforementioned technical problems, the present invention aims to provide a self-cleaning superhydrophobic coating for N-TiO2 photocatalytic surfaces and its fluorine-free preparation method. A loose, porous structure of N-TiO2 is constructed using a hydrothermal method to enhance the material's adsorption performance. Furthermore, stearic acid (STA) and polydimethylsiloxane (PDMS) are used to modify N-TiO2 for superhydrophobicity. Under visible light irradiation, the material simultaneously possesses superhydrophobicity and excellent photocatalytic performance, thereby achieving autonomous degradation and removal of pollutants.
[0008] To achieve the above objectives, the present invention is implemented through the following technical solution:
[0009] In a first aspect, this invention provides a fluorine-free preparation method for a self-cleaning superhydrophobic coating on an N-TiO2 photocatalytic surface, comprising the following steps:
[0010] S1. Urea is added to a solution of methanol, tetrabutyl titanate and acetylacetone and then subjected to ultrasonic treatment.
[0011] S2. After mixing the reaction solution obtained in step S1 with anhydrous ethanol evenly, perform hydrothermal reaction and centrifugation washing in sequence.
[0012] S3. The material obtained in step S2 is dried, ground and calcined in sequence to obtain a loose and porous N-TiO2 material;
[0013] S4. Dissolve N-TiO2 material in an organic solvent, sonicate it, add stearic acid for hydrophobic modification, and then centrifuge, wash, dry and grind it to obtain STA / N-TiO2 material.
[0014] S5. Disperse STA / N-TiO2 material and polydimethylsiloxane in ethyl acetate, then coat it onto a glass slide, and cure it to obtain a PDMS / STA / N-TiO2 coating.
[0015] Preferably, in step S1, the mass ratio of methanol, tetrabutyl titanate, and acetylacetone is 13:3:1 to 13:3.4:1. More preferably, the mass ratio of methanol, tetrabutyl titanate, and acetylacetone is 13:3.2:1.
[0016] Preferably, in step S2, the hydrothermal reaction temperature is 180–240°C and the reaction time is 3–6 hours.
[0017] More preferably, the hydrothermal reaction temperature is 220°C and the reaction time is 5 hours.
[0018] Preferably, in step S2, the organic solvent is ethanol; the specific steps of the centrifugal washing are: washing 2 to 3 times at a rate of 4300 to 5500 r / s and 2 to 4 min / time.
[0019] More preferably, in step S2, the specific steps of centrifugal washing are as follows: washing three times at a rate of 5000 r / s and 3 min / time.
[0020] Preferably, in step S3, the drying temperature is 80-110°C and the drying time is 10-13 hours.
[0021] More preferably, in step S3, the drying temperature is 100°C and the drying time is 12 hours.
[0022] Preferably, in step S3, the calcination is carried out by heating at a rate of 1-3°C / min to 450-550°C and holding for 2.5-3.5 hours.
[0023] More preferably, in step S3, the calcination is carried out by heating at a rate of 2°C / min to 500°C and holding for 3 hours.
[0024] Preferably, in step S4, the mass ratio of N-TiO2 to stearic acid is 1:1.1 to 1:1.3.
[0025] More preferably, in step S4, the mass ratio of N-TiO2 to stearic acid is 1:1.2.
[0026] Preferably, in step S4, the hydrophobic modification temperature is 65-75°C and the time is 2-3.5 hours.
[0027] More preferably, in step S4, the hydrophobic modification temperature is 70°C and the time is 3 hours.
[0028] Preferably, in step S4, the drying temperature is 75-85°C and the drying time is 6-10 hours.
[0029] More preferably, in step S4, the drying temperature is 80°C and the time is 8 hours.
[0030] Preferably, in step S5, the mass ratio of STA / N-TiO2 to polydimethylsiloxane is 1:1 to 3:2.
[0031] More preferably, in step S5, the mass ratio of STA / N-TiO2 to polydimethylsiloxane is 5:4.
[0032] Preferably, in step S5, the specific method of coating is as follows: after polishing, cleaning and drying the glass slide, the dispersion liquid is sprayed at a distance of about 15cm from the glass slide.
[0033] Preferably, in step S5, the curing temperature is 90–110°C and the curing time is 22–25 h.
[0034] More preferably, in step S5, the curing temperature is 100°C and the curing time is 24 hours.
[0035] In a second aspect, the present invention provides an N-TiO2 photocatalytic surface self-cleaning superhydrophobic coating material prepared by the above method.
[0036] The beneficial effects achieved by one or more technical solutions of the present invention are as follows:
[0037] (1) The preparation method provided by the present invention is simple and easy to control. The prepared PDMS / STA / N-TiO2 coating has a large contact angle with water, strong superhydrophobicity, good stability, and self-cleaning ability. It can effectively degrade organic pollutants such as methylene blue dye under visible light.
[0038] (2) The present invention adopts a fluorine-free modification method, which is more environmentally friendly and has better practical application feasibility. It can be widely applied to the surface of glass or walls to achieve self-cleaning of the exterior surfaces of buildings. Attached Figure Description
[0039] Figure 1 Infrared spectra of N-TiO2 materials with different nitrogen doping amounts prepared in Examples 1-3 of this invention and TiO2 materials prepared in Comparative Example 1.
[0040] Figure 2 The XRD patterns are those of N-TiO2 materials with different nitrogen doping amounts prepared in Examples 1-3 of this invention and TiO2 materials prepared in Comparative Example 1.
[0041] Figure 3 The figures show the photocatalytic degradation efficiency of methylene blue in Examples 1-3 of this invention, which were prepared by hydrothermal method to obtain N-TiO2 with different nitrogen doping amounts, in Comparative Example 1, which was prepared by hydrothermal method to obtain TiO2, and in Comparative Example 2, which was prepared by sol-gel method to obtain 3N-TiO2.
[0042] Figure 4 The graph shows the photocatalytic degradation efficiency of methylene blue by the 3N-TiO2 material prepared in Example 1 of this invention at different dosages.
[0043] Figure 5 The graph shows the photocatalytic degradation efficiency of methylene blue by the 2N-TiO2 material prepared in Example 2 of this invention at different dosages.
[0044] Figure 6 The graph shows the photocatalytic degradation efficiency of methylene blue by the 4N-TiO2 material prepared in Example 3 of this invention at different dosages.
[0045] Figure 7The figures show the hydrophobic angle test results for the PDMS / STA / N-TiO2 coatings. Figure (a) shows the PDMS / STA / 3N-TiO2 coating, (b) shows the PDMS / STA / 2N-TiO2 coating, (c) shows the PDMS / STA / 4N-TiO2 coating, (d) shows the PDMS / STA / TiO2 coating, (e) shows the PDMS / STA / 3N-TiO2 coating after two weeks of outdoor exposure, and (f) shows the PDMS / STA / 3N-TiO2(R) coating. Detailed Implementation
[0046] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0047] The instruments, equipment, and reagents used in this invention are as follows:
[0048] Table 1 Instruments and Equipment
[0049]
[0050]
[0051] Table 2 Main Reagents
[0052]
[0053] The present invention will be further described in detail below with reference to specific embodiments. It should be noted that the specific embodiments are explanations of the present invention and not limitations thereof.
[0054] Example 1 :
[0055] This embodiment provides a fluorine-free preparation method for a self-cleaning superhydrophobic coating material for N-TiO2 photocatalytic surfaces, including the following steps:
[0056] S1. Stir 40 mL of methanol, 8 g of tetrabutyl titanate, and 2.5 g of acetylacetone magnetically for 30 min at room temperature. Weigh 3 g of urea and add it to the obtained solution, then sonicate at room temperature for 30 min.
[0057] S2. Mix the solution with anhydrous ethanol evenly, transfer it to a polytetrafluoroethylene reactor, and perform a hydrothermal reaction in a 220℃ oven for 5 hours. After naturally cooling to room temperature, remove the material and wash it three times with anhydrous ethanol (5000r / s, 3min / time).
[0058] S3. Dry at 100℃ for 12 hours, grind, and calcine in a muffle furnace at 500℃ for 3 hours (heating rate 2℃ / min) to obtain loose and porous 3N-TiO2 material.
[0059] S4. Dissolve 3.7 g of 3N-TiO2 in 100 mL of ethanol and sonicate for 30 min. Add 4.5 g of stearic acid to the resulting solution and react at 70 °C for 3 h. Then wash the resulting material three times with anhydrous ethanol (5000 r / s, 3 min / time), dry at 80 °C, and grind to obtain STA / 3N-TiO2 material;
[0060] S5. Disperse 2.5g of STA / 3N-TiO2 material and 2mL of polydimethylsiloxane into 15mL of ethyl acetate, and magnetically stir the mixture for 30min at room temperature. Polish the glass slide with 1500# sandpaper, clean it with ethanol, and let it dry. Then, spray the dispersion onto the slide from approximately 15cm away. Finally, cure the PDMS / STA / 3N-TiO2 coating in a 100℃ oven for 24h.
[0061] Example 2 :
[0062] This embodiment provides a fluorine-free preparation method for a self-cleaning superhydrophobic coating material for N-TiO2 photocatalytic surfaces, including the following steps:
[0063] S1. Stir 40 mL of methanol, 8 g of tetrabutyl titanate, and 2.5 g of acetylacetone magnetically for 30 min at room temperature. Weigh 2 g of urea and add it to the obtained solution, then sonicate at room temperature for 30 min.
[0064] S2. Mix the solution with anhydrous ethanol evenly, transfer it to a polytetrafluoroethylene reactor, and perform a hydrothermal reaction in a 220℃ oven for 5 hours. After naturally cooling to room temperature, remove the material and wash it three times with anhydrous ethanol (5000r / s, 3min / time).
[0065] S3. Dry at 100℃ for 12 hours, grind, and calcine in a muffle furnace at 500℃ for 3 hours (heating rate 2℃ / min) to obtain loose and porous 2N-TiO2 material.
[0066] S4. Dissolve 3.7 g of 2N-TiO2 in 100 mL of ethanol and sonicate for 30 min. Add 4.5 g of stearic acid to the resulting solution and react at 70 °C for 3 h. Then wash the resulting material three times with anhydrous ethanol (5000 r / s, 3 min / time), dry at 80 °C, and grind to obtain STA / 2N-TiO2 material;
[0067] S5. Disperse 2.5g of STA / 2N-TiO2 material and 2mL of polydimethylsiloxane into 15mL of ethyl acetate, and magnetically stir the mixture for 30min at room temperature. Polish the glass slide with 1500# sandpaper, clean it with ethanol, and let it dry. Then, spray the dispersion onto the slide from approximately 15cm away. Finally, cure the PDMS / STA / 2N-TiO2 coating in a 100℃ oven for 24h.
[0068] Example 3 :
[0069] This embodiment provides a fluorine-free preparation method for a self-cleaning superhydrophobic coating material for N-TiO2 photocatalytic surfaces, including the following steps:
[0070] S1. Stir 40 mL of methanol, 8 g of tetrabutyl titanate, and 2.5 g of acetylacetone magnetically for 30 min at room temperature. Weigh 4 g of urea and add it to the obtained solution, then sonicate at room temperature for 30 min.
[0071] S2. Mix the solution with anhydrous ethanol evenly, transfer it to a polytetrafluoroethylene reactor, and perform a hydrothermal reaction in a 220℃ oven for 5 hours. After naturally cooling to room temperature, remove the material and wash it three times with anhydrous ethanol (5000r / s, 3min / time).
[0072] S3. Dry at 100℃ for 12 hours, grind, and calcine in a muffle furnace at 500℃ for 3 hours (heating rate 2℃ / min) to obtain loose and porous 4N-TiO2 material.
[0073] S4. Dissolve 3.7 g of 4N-TiO2 in 100 mL of ethanol and sonicate for 30 min. Add 4.5 g of stearic acid to the resulting solution and react at 70 °C for 3 h. Then wash the resulting material three times with anhydrous ethanol (5000 r / s, 3 min / time), dry at 80 °C, and grind to obtain STA / 4N-TiO2 material;
[0074] S5. Disperse 2.5g of STA / 4N-TiO2 material and 2mL of polydimethylsiloxane into 15mL of ethyl acetate, and magnetically stir the mixture for 30min at room temperature. Polish the glass slide with 1500# sandpaper, clean it with ethanol, and let it dry. Then, spray the dispersion onto the slide from approximately 15cm away. Finally, cure the PDMS / STA / 4N-TiO2 coating in a 100℃ oven for 24h.
[0075] Comparative Example 1 :
[0076] The difference from Examples 1-3 is that: this comparative example uses analytical grade TiO2 purchased from Shanghai McLean Biochemical Technology Co., Ltd. as the undoped nitrogen monomer to replace the N-TiO2 in the examples for comparison, and tests the photocatalytic performance and the superhydrophobic performance of the coating.
[0077] Comparative Example 2 :
[0078] This embodiment provides a method for preparing 3N-TiO2(R) using the sol-gel method:
[0079] S1. Stir 40 mL of anhydrous ethanol, 8 g of tetrabutyl titanate, and 1.5 mL of glacial acetic acid magnetically for 1 h at room temperature. Weigh 3 g of urea, dissolve it in 5 mL of distilled water, and add it to the obtained solution;
[0080] S2. Adjust the pH value with concentrated nitric acid until a yellow transparent sol is formed, then stir magnetically for 2 hours and let stand until the sol appears.
[0081] S3. After drying the obtained gel in an oven at 100℃ for 4 hours, place it in a muffle furnace and calcine it at 500℃ for 2 hours (heating rate 5℃ / min) to obtain 3N-TiO2(R) material.
[0082] Example 4 :
[0083] Fourier transform infrared (FTIR) tests were performed on the N-TiO2 photocatalytic surface self-cleaning superhydrophobic coating materials with different nitrogen doping amounts obtained in Examples 1-3 and the undoped nitrogen-containing TiO2 monomer obtained in Comparative Example 1.
[0084] The results are as follows Figure 1 As shown, in the range of 400-700cm -1 The absorption peak at 1045 cm⁻¹ originates from the Ti-O bond in the catalyst. -1 An absorption peak appeared, which is due to the presence of O-Ti-N bonds in the N-TiO2 sample, indicating the presence of nitrogen in the prepared catalyst and the effective binding of nitrogen with TiO2. The absorption peak occurred in the 3000–3500 cm⁻¹ range. -1 The absorption peak that appears is the stretching vibration absorption peak of the OH bond, which originates from the water molecules present in the sample.
[0085] Example 5 :
[0086] XRD tests were performed on the N-TiO2 photocatalytic materials with different nitrogen doping amounts obtained in Examples 1-3 and the undoped TiO2 monomer obtained in Comparative Example 1.
[0087] The results are as follows Figure 2As shown, a comparison with the standard card (PDF#04-005-4859) reveals that the N-TiO2 obtained in this experiment are all anatase crystals. Further observation shows that the diffraction peaks of the samples are sharp, indicating that the prepared nitrogen-doped titanium dioxide samples have high crystallinity.
[0088] Example 6 :
[0089] In this embodiment, methylene blue (MB) organic dye was used to simulate organic pollutants. The photocatalytic degradation performance of the N-TiO2 photocatalytic surface self-cleaning superhydrophobic coating materials with different nitrogen doping amounts obtained in Examples 1-3, the undoped nitrogen monomer TiO2 obtained in Comparative Example 1, and the 3N-TiO2(R) material prepared by the sol-gel method in Comparative Example 2 were tested.
[0090] 100 mL of a 20 ppm MB solution was added to a beaker. The materials prepared in Examples 1-3 and Comparative Examples 1 and 2 were added to the above solution in different beakers and stirred for 30 min to reach stability and adsorption equilibrium. The mixture was then irradiated with a xenon lamp, and the MB solution was collected every 0.5 h. After filtration, the absorbance of the MB solution was measured. The degradation efficiency was calculated using formula (I). Finally, the degradation status of the dye was determined by ultraviolet spectrophotometry.
[0091] D%=(C0-C) / C0×100%Equation (Ⅰ)
[0092] Where D is the degradation rate, C0 is the initial absorbance value, and C is the average absorbance value at different sampling times.
[0093] The results are as follows Figure 3 As shown, compared with pure TiO2 catalysts, nitrogen-doped N-TiO2 exhibited better degradation efficiency for methylene blue after 120 min. Among them, the catalytic effect of 3N-TiO2 synthesized by the hydrothermal method was superior to that of 3N-TiO2(R) prepared by the sol-gel method. This may be because the operation process of the sol-gel method is not easy to control, resulting in a less effective nitrogen doping effect compared to the hydrothermal method, thus affecting the photocatalytic efficiency. The 3N-TiO2 catalyst prepared by the hydrothermal method showed the best degradation effect on methylene blue, achieving a degradation efficiency of 91.32% within 120 min.
[0094] Example 7 :
[0095] In this embodiment, methylene blue (MB) organic dye was used to simulate organic pollutants to evaluate the photocatalytic degradation performance of STA / 3N-TiO2 coating with different dosages.
[0096] 100 mL of a 20 ppm MB solution was added to a beaker, and the STA / nN-TiO2 coating material was then added to the solution and stirred for 30 min to reach stability and adsorption equilibrium. The mixture was then irradiated with a xenon lamp, and the MB solution was collected every 0.5 h. After filtration, the absorbance of the MB solution was measured. The degradation efficiency was calculated using equation (I). Finally, the degradation status of the dye was determined by ultraviolet spectrophotometry.
[0097] The results are as follows Figure 4-6 As shown. Figure 4 When 0.02–0.04 g of STA / 3N-TiO2 was added to the methylene blue solution, it showed a significant removal effect on methylene blue. The highest removal efficiency of methylene blue was achieved when the dosage was 0.03 g, with a removal rate of 91.32% after 120 min of light irradiation.
[0098] like Figure 5 When 0.02–0.04 g of STA / 2N-TiO2 was added to the methylene blue solution, it showed a significant removal effect on methylene blue. The highest removal efficiency of methylene blue was achieved when the dosage was 0.03 g, with a removal rate of 84.47% after 120 min of light irradiation.
[0099] like Figure 6 When 0.02–0.04 g of STA / 4N-TiO2 was added to the methylene blue solution, it showed a significant removal effect on methylene blue. Among them, the highest removal efficiency of methylene blue was achieved when the dosage was 0.03 g, with a removal rate of 85.48% after 120 min of light irradiation.
[0100] Example 8 :
[0101] In this embodiment, the water contact angle of the N-TiO2 photocatalytic self-cleaning superhydrophobic coating plates with different nitrogen doping amounts obtained in Examples 1-3 was measured using a surface contact angle measuring instrument.
[0102] The results are as follows Figure 5 As shown, the contact angle of the PDMS / STA / 3N-TiO2 coating prepared in Example 1 is 170.9°; and the contact angle of the PDMS / STA / 3N-TiO2 coating prepared in Example 1 after two weeks of outdoor exposure is 158.4°.
[0103] The contact angle of the PDMS / STA / 2N-TiO2 coating prepared in Example 2 was 159.7°;
[0104] The contact angle of the PDMS / STA / 4N-TiO2 coating prepared in Example 3 was 157.4°;
[0105] The contact angle of the PDMS / STA / TiO2 coating prepared in Comparative Example 1 was 153.8°;
[0106] The contact angle of the PDMS / STA / 3N-TiO2(R) coating prepared in Comparative Example 2 was 156.8°.
[0107] The water contact angle measurements show that the coated plates prepared in Examples 1-3 and Comparative Examples 1 and 2 all exhibit water contact angles greater than 150°, demonstrating excellent superhydrophobic properties. However, the surface water contact angles of Examples 1-3 are all greater than those of the comparative examples. This may be due to the incorporation of nitrogen via a hydrothermal method, which alters the properties of the nanomaterials and enhances their hydrophobicity. Furthermore, after two weeks of outdoor exposure testing, the coating still exhibits excellent superhydrophobic properties, proving that the coating material has good stability.
[0108] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A fluorine-free preparation method for a 3N-TiO2 photocatalytic surface self-cleaning superhydrophobic coating, characterized in that, Includes the following steps: S1. Stir 40 mL of methanol, 8 g of tetrabutyl titanate and 2.5 g of acetylacetone magnetically for 30 min at room temperature; weigh 3 g of urea and add it to the obtained solution, and sonicate at room temperature for 30 min. S2. Mix the solution with anhydrous ethanol evenly, transfer it to a polytetrafluoroethylene reactor, and perform a hydrothermal reaction in a 220°C oven for 5 hours. After naturally cooling to room temperature, remove the material and wash it three times by centrifugation with anhydrous ethanol. S3. Dry at 100℃ for 12 h, grind, and calcine in a muffle furnace at 500℃ for 3 h with a heating rate of 2℃ / min to obtain a loose and porous 3N-TiO2 material. S4. Dissolve 3.7 g of 3N-TiO2 in 100 mL of ethanol and sonicate for 30 min. Add 4.5 g of stearic acid to the resulting solution and react at 70 °C for 3 h. Then wash the resulting material three times with anhydrous ethanol by centrifugation, dry it at 80 °C, grind it, and obtain STA / 3N-TiO2 material. S5. Disperse 2.5 g of STA / 3N-TiO2 material and 2 mL of polydimethylsiloxane into 15 mL of ethyl acetate, and stir the mixture magnetically for 30 min at room temperature; polish the glass slide with 1500# sandpaper and clean it with ethanol and let it dry; then, spray the dispersion at a distance of about 15 cm from the glass slide; finally, cure the PDMS / STA / 3N-TiO2 coating in an oven at 100℃ for 24 h.
2. A 3N-TiO2 photocatalytic surface self-cleaning superhydrophobic coating material, characterized in that, Obtained by the preparation method described in claim 1.